Search for a standard model Higgs boson in the mass range 200-600 GeV in the H→ZZ→l+l−qq [bar] decay channel with the ATLAS detector* - Aad, Georges; Anders, Gabriel; Anders, Christoph; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physics letters, 2012)
A search for a heavy Standard Model Higgs boson decaying via H→ZZ→ℓ+ℓ−qq¯, where ℓ=e or μ, is presented. The search uses a data set of pp collisions at s=7 TeV, corresponding to an integrated luminosity of 4.7 fb−1 collected in 2011 by the ATLAS detector at the CERN LHC. No significant excess of events above the estimated background is found. Upper limits at 95% confidence level on the production cross section of a Higgs boson with a mass in the range between 200 and 600 GeV are derived. A Standard Model Higgs boson with a mass in the range 300 GeV⩽mH⩽322 GeV or 353 GeV⩽mH⩽410 GeV is excluded at 95% CL. The corresponding expected exclusion range is 351 GeV⩽mH⩽404 GeV at 95% CL.
Im Titel werden "+" und "-" hochgestellt
ATLAS Collaboration: G. Aad, C.F. Anders, G. Anders, V. Andrei, Y. Davygora, T. Dietzsch, C. Geweniger, P. Hanke, M. Henke, G. Kasieczka, A. Khomich, E.-E. Kluge, A. Kugel, V. Lang, V. Lendermann, F. Lepold, R. Maenner, K. Meier, F. Mueller, R. Narayan, S. Poddar, S. Schaetzel, V. Scharf, S. Schmitt, A. Schöning, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und weitere]
Gesehen am 28.11.2018